The synergistic effect of the RuO2 nanoparticle-decorated V2O5 heterostructure for high-performance asymmetric supercapacitors. (28th July 2021) - Palani, N. S.; Kavitha, N. S.; Venkatesh, K. S.; Ashok Kumar, K.; Senthilkumar, M.; Pandurangan, A.; Ilangovan, R.
Abstract : Schematic illustration of a 3 wt% RuO2 –V2 O5 //AC asymmetric supercapacitor device Abstract : Two-dimensional RuO2 nanoparticle-decorated V2 O5 nanoflakes are successfully synthesized by a simple solvothermal method. The synthesized RuO2 -decorated V2 O5 nanocomposite electrode exhibited a high charge–discharge capacity with an excellent cyclic retention of 94.6% over 10 000 cycles. Specifically, the 3 wt% RuO2 in V2 O5 (R2) nanocomposite electrode showed a high specific capacitance of 421 F g −1 at a current density of 1 A g −1 in a three-electrode system. The specific capacitance of the R2 nanocomposite is almost 3-fold higher than that of pure V2 O5 nanosheets in the three-electrode system. An energy density of 29 Wh kg −1 was achieved in a two-electrode system at a power density of 816 W kg −1 in an R2 based asymmetric supercapacitor device. The energy density and power density of the RuO2 –V2 O5 nanocomposite are higher than those of previously reported V2 O5 nanostructured asymmetric supercapacitors.